2017
DOI: 10.1186/s12879-017-2610-7
|View full text |Cite
|
Sign up to set email alerts
|

Space and space-time distributions of dengue in a hyper-endemic urban space: the case of Girardot, Colombia

Abstract: BackgroundDengue is a widely spread vector-borne disease. Dengue cases in the Americas have increased over the last few decades, affecting various urban spaces throughout these continents, including the tourism-oriented city of Girardot, Colombia. Interactions among mosquitoes, pathogens and humans have recently been examined using different temporal and spatial scales in attempts to determine the roles that social and ecological systems play in dengue transmission. The current work characterizes the spatial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…On the other hand, low elevations or sea level (coastal areas) maintain a high correlation with the Zika presence of cases (r=-0.454 p <0.000) such findings are consistent with other studies. 12,17,18 Previous studies have shown that density population is an important factor in the transmission of ETV's such as Zika, which is consistent with the moderate correlation observed (r=0.311 p<0.005) which indicates that Zika cases are correlated with high population densities where there is supposed to be a greater Zika transmission of cases. 12,19,20 The variables identified by this study directly affect the vector biology and therefore the occurrence of outbreaks, so it is very important to conduct more research where entomological information.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, low elevations or sea level (coastal areas) maintain a high correlation with the Zika presence of cases (r=-0.454 p <0.000) such findings are consistent with other studies. 12,17,18 Previous studies have shown that density population is an important factor in the transmission of ETV's such as Zika, which is consistent with the moderate correlation observed (r=0.311 p<0.005) which indicates that Zika cases are correlated with high population densities where there is supposed to be a greater Zika transmission of cases. 12,19,20 The variables identified by this study directly affect the vector biology and therefore the occurrence of outbreaks, so it is very important to conduct more research where entomological information.…”
Section: Discussionsupporting
confidence: 81%
“…Several articles examining patterns of DENF in Colombia have recognized outdated population census being a critical issue that could affect the findings of their research. [73][74][75][76][77][78] Until more recent census are available, different population growth models could address this issue, or relying on disaggregated population projection, using dasymetric mapping. 79,80 Third, including vector surveillance data (presence/absence) in each neighborhood would improve the accuracy of the relative risk estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In northern Argentina, Rotela et al 35 studied the spread of a dengue outbreak based on space-time grouping of cases. Space-time analyses of dengue cases have been performed in Thailand 36 , Vietnam 37 , and Colombia 38 . In Brazil, three publications were identified that discuss dengue using SaTScan: one analyzes dengue cases in the city of Lavras, Minas Gerais State, between 2007 and 2010 39 ; the second detects clusters based on dengue seasonality in Brazilian municipalities from 2007 to 2011 40 ; and the third, by Vicente et al 41 , analyzes the determination of clusters and factors associated with the spread of dengue during the first epidemic involving DENV-4 in the city of Vitória, Espírito Santo State.…”
Section: Introductionmentioning
confidence: 99%